Comparision between laser and sandblasting surface treatments on push-out bond strength of fiber posts to root canals - abdolrahim davari; farnaz farahat; haleh davoudi (Tehran University of Medical Sciences, 2023)
Background and Aims: Insufficient adhesion between fiber post and root canal is the main reason for the failure of the restoration and the fiber post surface treatment can imprive the bond strength. Additionally, there is disagreement about the ideal method of preparation to achieve the desired bond. The aim of this study was to compare the effect of two surface treatment methods on push-out bond strength of fiber posts to root canals. Materials and Methods: In this study, 45 healthy incisor teeth underwent root canal treatment. After preparing the post space, they were divided into 3 groups of 15, based on the surface treatment methods of the fiber post. In the first group as control group, no surface treatment was done on the fiber post. In the second and third groups, sandblasting with Cojet sand particles and 810 nm diode laser were used for surface treatment, respectively. Then, fiber posts were placed in all root channels by a self-adhesive resin cement. Then, the roots were cut in such a way that from each, 3 pieces with a thickness of 1.5 mm were obtained. Finally, the push-out bond strengths were measured using a universal testing machine. Data were analyzed by ANOVA using SPSS software. The level of significance was considered at P<0.05. Results: The average bond strengths in three groups were as follows: control group, 2.877 ±1.430, sandblast group 6.318±3.444, and laser 4.224 ±1.890 MPa ± SD. The difference in the bond strength between the sandblast group and the control group was significant (P=0.001). However, the average of the bond strength of laser group was not significantly different from the control group. (P=0.03). Conclusion: The findings of this study showed that unlike diode laser radiation, the use of Cojet sand particles for sandblasting the fiber post surfaces significanlty improved the bond strength.